The Squatchicorns - Potter, Ellen, 1963- (Potter, Ellen, 1963- Big Foot and Little Foot, 2019)
A tribe of odd-looking Sasquatches flee their cursed cave and take refuge with Hugo, but when Hugo invites Nobb, one of the strange squidges, to Boone's birthday party, the result is near-disaster.